MENEROPONG KEPASTIAN PENETAPAN STATUS TERSANGKA DALAM KUHAP BARU - Erwin Susilo (Al-Adl : Jurnal Hukum, 2026)
The primary focus of this study is to examine the certainty of suspect status and case resolution at the pre-adjudication stage under the New Indonesian Criminal Procedure Code (KUHAP). The research addresses two principal issues: first, the regulation of case resolution at the stages of investigation and prosecution under both the Old KUHAP and the New KUHAP; and second, the critique and reconstruction of pre-adjudication case resolution models necessary to prevent the recurrence of injustices that characterized the Old KUHAP regime. This study employs normative legal research using four approaches, namely statutory, conceptual, comparative, and case-based approaches. The findings reveal that although the New KUHAP has introduced a more structured coordination mechanism between Investigators and Public Prosecutors within the framework of an Integrated Criminal Justice System, it continues to exhibit legal lacunae. These shortcomings are evident in the absence of regulation concerning the legal consequences of exceeding the prescribed time limit for the initial examination of case files (Article 61), as well as the lack of clarity regarding the commencement point (dies a quo) for calculating the time period for case transfer to the court (Articles 70 and 75). Such conditions may result in the prolonged and uncertain status of suspects, thereby contravening the presumption of innocence, the principle of legal certainty (litis finiri oportet), and the principle of a speedy, simple, and cost-effective trial. This study recommends normative reconstruction through the harmonization of time-limit regulations, the clarification of legal consequences, and the strengthening of judicial oversight through pretrial mechanisms to ensure adequate legal protection for suspects.